2012
DOI: 10.1167/12.4.6
|View full text |Cite
|
Sign up to set email alerts
|

The color constancy of three-dimensional objects

Abstract: Human color constancy has been studied for over one hundred years, and there is extensive experimental data for the case where a spatially diffuse light source illuminates a set of flat matte surfaces. In natural viewing, however, three-dimensional objects are viewed in three-dimensional scenes. Little is known about color constancy for three-dimensional objects. We used a forced-choice task to measure the achromatic chromaticity of matte disks, matte spheres, and glossy spheres. In all cases, the test stimuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 68 publications
(93 reference statements)
5
33
2
Order By: Relevance
“…Furthermore, the question of how disparity and luminance contribute to pattern recognition is formally related to the question of how different sources of information contribute to the detection of threshold stimuli, and specifically of whether subthreshold summation takes place (e.g. Meinhardt, Persike, Mesenholl, & Hagemann, 2006), and to the question of how changes in individual dimensions contribute to the appearance of complex stimuli (Landy et al, 1995; To, Baddeley, Troscianko, & Tolhurst, 2011; To, Lovell, Troscianko, & Tolhurst, 2008). In all of these contexts, it is possible to compare the performance which is observed when combined stimuli are presented with the performance which can be predicted based on the results of the single-modality stimuli assuming independent processing of the two dimensions and linear combination of the responses.…”
Section: Experiments 3: Rds Patternsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the question of how disparity and luminance contribute to pattern recognition is formally related to the question of how different sources of information contribute to the detection of threshold stimuli, and specifically of whether subthreshold summation takes place (e.g. Meinhardt, Persike, Mesenholl, & Hagemann, 2006), and to the question of how changes in individual dimensions contribute to the appearance of complex stimuli (Landy et al, 1995; To, Baddeley, Troscianko, & Tolhurst, 2011; To, Lovell, Troscianko, & Tolhurst, 2008). In all of these contexts, it is possible to compare the performance which is observed when combined stimuli are presented with the performance which can be predicted based on the results of the single-modality stimuli assuming independent processing of the two dimensions and linear combination of the responses.…”
Section: Experiments 3: Rds Patternsmentioning
confidence: 99%
“…see Landy, Maloney, Johnston, & Young, 1995), in the estimation of slant (e.g. Backus & Banks, 1999; Backus, Banks, van Ee, Crowell, & Crowell, 1999; Banks & Backus, 1998; Girshick & Banks, 2009; Hillis, Ernst, Banks, & Landy, 2002; Hillis, Watt, Landy, & Banks, 2004; Knill & Saunders, 2003), and in the perception of shape (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The desire to get a detailed map of phenomenal colours led researchers to examine the structure of colour space in very controlled viewing conditions, usually with the goal of ensuring the adequate replication of colours, for example, in printing or on screen. In the last two decades this approach has been extended to begin mapping experiences of colours on backgrounds of varied colour (Ekroll, Faul, & Niederee, ; Ekroll, Faul, Niederee, & Richter, ) in more complex stimulus configurations (Ekroll et al, ) containing shadows (Logvinenko, ) and with 3D objects (Xiao, Hurst, MacIntyre, & Brainard, ). It might be the case that more than three dimensions are needed to map the colour experiences elicited by complex stimuli (Logvinenko, , ; Tokunaga & Logvinenko, ).…”
Section: How Is Consciousness Operationalised In Lab Conditionsmentioning
confidence: 99%
“…The studies of illumination and material inluence on renderings revealed that observers perceive the colours that are reproduced in renderings diferently as they are predicted by algorithms of various rendering methods [41][42][43].…”
Section: Computer Simulationmentioning
confidence: 99%
“…Xiao and colleagues [41,42] demonstrated that by diferent illumination conditions, there are diferences in colour perception between graphical simulations of mate disks and specular spheres. Yang and colleagues [44,45] presented an expanded study of the correlation between colour perception of surfaces and illumination cues.…”
Section: Computer Simulationmentioning
confidence: 99%